Growth patterns and associated factors among children receiving long-term inhaled corticosteroid therapy for asthma. A hospital-based prospective observational cohort study. - Ankit Kumar Gupta; Alok Singh; Thakur Shivani (SJ Pediatrics and Child Health Africa, 2026)
BackgroundInhaled corticosteroids (ICS) are central to persistent asthma management in children, but prolonged exposure may affect linear growth, particularly at higher doses or with repeated systemic corticosteroid use. ObjectivesTo describe growth patterns and identify factors associated with reduced height velocity among children receiving long-term ICS therapy for asthma. MethodsThis prospective observational cohort study included 100 children aged 5–14 years at RSDKS Government Medical College, Ambikapur, Chhattisgarh, India. Demographic characteristics, asthma severity and control, corticosteroid exposure, adherence, and anthropometric measurements were recorded. Height, weight, and corresponding z scores were assessed at baseline, 6 months, and 12 months. Reduced height velocity was defined as below the age- and sex-specific 25th percentile. Associated factors were evaluated using logistic regression. ResultsThe mean age was 9.2 ± 2.6 years, and 61.0% were boys. Mean annual height velocity was 5.3 ± 1.1 cm/year, and the mean height-for-age z score declined from −0.39 ± 0.86 at baseline to −0.48 ± 0.89 at 12 months (p